Time-varying Formation Tracking for Second-order Multi-agent Systems Subjected to Switching Topology and Input Saturation - Liu, Jing; Fang, Jian-an; Li, Zhen; He, Guang (International journal of control, automation, and systems, 2020)
This paper addresses the problem of time-varying formation tracking for a kind of second-order multi-agent systems with a switching topology, in which the dynamics of agents are modeled by double integrators and harmonic oscillators respectively. The control input of each agent is subject to saturation. First, depending on the low-gain state feedback technique, an algorithm is designed to solve semi-global time-varying formation tracking problem, where feasibility condition of formation tracking is introduced. Then, by utilizing the Lyapunov function and low-gain feedback theory, it is proved that second-order multi-agent system with a switching topology achieves the specified semi-global time-varying formation tracking if some sufficient conditions hold. Further, as an extension, jointly connected switching topology is considered, and the corresponding formation tracking problem is also explored. Subsequently, several simulation examples is worked out for illustration.